Pengaruh Dana Desa terhadap Kemiskinan: Studi Tingkat Kabupaten/Kota di Indonesia - Tri Angga Sigit; Ahmad Kosasih (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
National development in general aims to improve people's welfare as measured by poverty indicators. In reducing poverty, one focus of the government is to reduce poverty in rural areas that have a higher percentage than urban areas. One of the government spending aimed at reducing poverty in rural areas is the Village Fund. This study aims to determine the effect of the Village Fund on poverty at the Regency/City level in Indonesia. This study uses quantitative data that focuses on economic variables consisting of the Total Poor Population as the dependent variable and the Village Fund as the main independent variable. In addition, Village Fund Allocation, Gross Regional Domestic Product, and Capital Expenditures are used as other independent variables. As a material for analysis and compiling recommendations, qualitative data in this study were used in the form of in-depth interviews with the Directorate General of Fiscal Balance and the Fiscal Policy Office. The analytical method used is panel data regression with the Fixed Effect Model. The result shows that the Village Fund variable has a negative effect on the Total Poor Population. This shows that the Village Fund is able to effectively reduce the number of poor people. However, based on the results of in-depth interviews, there are at least three aspects of the Village Fund policy that need to be improved namely covering improvements to the formulation aspects, aspects of strengthening supervision, and aspects of increasing innovation in the use of Village Funds.